Treinamento muscular do assoalho pélvico no tratamento fisioterapêutico da incontinência urinária por deficiência esfincteriana - Yamamoto, Deborah Mari [UNIFESP] (2019)
Aim: To evaluate the effets of the pelvic floor muscle training (PFMT) in the treatment of urinary incontinence (UI) in patients with intrinsic sphincter deficiency (ISD). Methods:It was included in this study 15 women diagnosed with UI with ISD through the urodynamic study, which was considered the Valsalva leak point pressure (VLPP) less than or equal to 60 cmH2O. Women previously treated with PFMT, surgery for UI repair, presence of neurological disorders, chronic degenerative diseases that can affect the nervous and muscular tissues, presence of genital prolapse stage III and IV or absence of pelvic floor muscle (PFM) contraction due to complete denervation were not included in this trial. The patients were advised about the perineal awareness and were instructed to take the correct contraction of the perineal muscles before starting the program of the PFMT, which consisted of three sets of exercises daily of eight maximum voluntary contractions held for 6 s to 10 s, with 1:1 s rest between each contraction, followed by three to five fast contractions in a row. Firstly, all women have received instructions and have performed the protocol at the ambulatory of physiotherapy and then were instructed to perform at home for twelve weeks. Furthermore, it was taught the perineal contraction previously situations of increased intra-abdominal pressure (The Knack). The outcome measures were the functional assessment of PFM (Oxford scale and endurance), voiding diary, pad test, Incontinence Quality of Life Questionnaire (I-QoL) and The International Consultation on Incontinence Questionnaire – Short Form (ICIQ-SF). All procedures were performed at the beginning and end of the treatment.The Wilcoxon Test and the software Minitab version 16.1 were used for the calculation of the initial and final analysis.Results:It was exdluded 5 women. The mean of VLPP was 44,20 cmH2O (±11,18 cmH2O). There was no improvement in the functional assessment of the PFM (Oxford with p = 0,059 and endurance with p = 0,138)and criteria of the voiding diary after the exercises, frequency (p = 0,919), nocturia (p = 0,554), urinary loss (p = 0,097) and amount of protector (p = 0,866). There was a significant decrease on pad test (p = 0,035). The quality of life ICIQ-SF showed improvement (p =0,09), as well as I-QoL in the psychosocial impact domain (p = 0,035). Conclusion: The PFMT showed significant improvement in pad test, ICIQ-SF questionnaire and in the psychosocial impact domain of I-QoL for women with UI with ISD.